If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1) = 4x + 6 Reorder the terms: 2(-1 + 3x) = 4x + 6 (-1 * 2 + 3x * 2) = 4x + 6 (-2 + 6x) = 4x + 6 Reorder the terms: -2 + 6x = 6 + 4x Solving -2 + 6x = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 6x + -4x = 6 + 4x + -4x Combine like terms: 6x + -4x = 2x -2 + 2x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + 2x = 6 + 0 -2 + 2x = 6 Add '2' to each side of the equation. -2 + 2 + 2x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 6 + 2 2x = 6 + 2 Combine like terms: 6 + 2 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 10x-20=5x+3 | | 6x+1=4x+6 | | 13-25x=14-66 | | 7/2k^2-k-4/7=0 | | 4-x/25 | | 9x+30=3x+162 | | 3y-4x=25 | | 2x^2-2x-40=-16 | | 8y-17=y+4 | | 2xyd*x+(x^2-1)d*y=0 | | (96*x)+(12*y)=85 | | 2.9-x=7.2 | | x/19.7=0.6913755838 | | n+4.7=-4.6 | | 3(a-17)=90 | | -4(2t+3)=-36 | | 3(x-7)+5=3x-15 | | (x-3x)(x+9)=-27 | | -10(s+2)=9 | | 2(x-8)+5=2x-11 | | 112+14x=y | | .5(x-22)=16+5x | | x=300eilrst | | 18+5.50x=11+6.75x | | 6(3s+9)=252 | | x=300liters | | y=4*3-9 | | 9(6+p)=36 | | 6x+16=10x+3 | | 4(a-4)=56 | | 6x+3.5=6.7 | | 4u+8v=-3v+2u |